(untitled) (Journal of the College of Education for Women, 2019)
Ubikh is one of the most important tribes of the Northwest Caucasus and has a long history. Naturally, rebukes are an integral part of the Caucasus region. Their people were able to confront the Russian invasion of their lands like the rest of the Caucasus tribes to defend their existence, freedom and the right to build their independent state, but they were not able to resist the great Russian military progress they achieved on all sides. For the territory that belonged to Persia and the Ottoman Empire and ended the resistance of the Meridian movement in the Northeast Caucasus, the Russians left only the weak resistance of the tribes of the Northwest Caucasus led by the rebuke after Russia managed to eliminate all resistance movements in the Caucasus In the Northwest Caucasus, the research was based on an integrated historical approach based on the presentation of historical material, and linked them objectively taking into account the use of descriptive method and analysis of events, at both the political and military levels in the Ubik tribes in the Caucasus